Aeronautas: expectativas, temores... diante da proximidade da velhice, da morte - Bertulucci, Sandra Fabiola Estigarribia Salinas (2016)
The old age becomes a concern especially when people are around 60. Although there are advancing studies aimed at old age issues, it seems that few are those that deal with the problems faced by Aviation professionals when they approach retirement. The purpose of this paper is to review how airmen mean their career when they reach 60 or more, which also articulates the issue of health, physical, subjective-psychological and social well-being, family, friends relations. Retirement in its implications can be traumatic for many airmen lives, as well as their expectations, or even a certain fear, before the thought of finitude/death. The methodology started with a survey and review of theoretical texts of journals, books, some manuals of aeronautical fields, as well as the interpretation of responses to the application of a sociodemographic questionnaire, semi-structured, with closed and open questions to airmen. This empirical allowed recovering significant statements about the feelings of airmen around their removal from a delightful occupation, down to the status of "forced inactivity", the change of status within the professional hierarchy, with results from its subjectivity, in relations with family, friends. Concluding, their protests as the possibility of extension of their working time, a continuing education, and leisure together their families in this time of their lives